Socioeconomic status and different forms of rhinitis in Swedish adults - Muwada Bashir Awad Bashir; Teet Pullerits; Linda Ekerljung; Helena Backman; Göran Wennergren; Hannu Kankaanranta; Bright I. Nwaru (Clinical and Translational Allergy, 2024)
Abstract Background Rhinitis encompasses diverse forms. Each form has distinct pathophysiology and clinical manifestations and may be influenced by differential risk factors. The association between socioeconomic status (SES) and different forms of rhinitis remains poorly understood. Our aim was to examine SES variations in allergic rhinitis, chronic rhinitis, and chronic rhinosinusitis in adults. Methods Based on a 2016 postal questionnaire survey within the West Sweden Asthma Study, we analyzed data from 36,213 subjects aged 16–75 years. The measures of SES were levels of education and occupation. Adjusted logistic regression was used to examine associations between SES and the rhinitis outcomes. Results Attaining a secondary school and tertiary education, compared to a primary school, were associated with increased risk of allergic rhinitis (secondary OR 1.33, 95% CI 1.22–1.45; tertiary 1.54, 1.41–1.69) and chronic rhinitis (secondary 1.18, 1.08–1.29; tertiary 1.17, 1.06–1.28). The influence of occupation was consistent with respect to allergic rhinitis. For instance, compared to the lowest occupational skill level, the highest level (OR 1.24, 95% CI 1.04–1.48) and the lower high occupation levels (1.24, 1.04–1.49) were associated with an increased risk of allergic rhinitis. No significant link was found between education and chronic rhinosinusitis or between occupation levels and risk of either chronic rhinitis or chronic rhinosinusitis. Conclusion Individuals with higher education and those at higher occupational levels may be at higher risk of having different forms of rhinitis than those at lower education and occupation levels. Assessment of rhinitis burden via SES can be one strategy to develop preventive strategies.